Analisis Pemasaran Tandan Buah Segar Kelapa Sawit Di Kabupaten Kutai Kartanegara (Studi Kasus Pada Petani Swadaya Kecamatan Muara Muntai) - Nugroho, Agung Enggal (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2015)
The purpose of this study was to determine: (1) marketing channels palm oil, (2) share of the farmers and marketing agencies and , (3) the main problems by farmers in the district of Muara Muntai.The results of this study indicate that in Muara Muntai District there are two types of FFB marketing channels, which is a two-level and three level channel. At two level channel, share received by farmers amounted to 76.15%, traders amounted to 17.96%, and the owner SPB by 5.88%. While at the three levels of marketing channels, the share received by farmers amounted to 73.53%, amounting to 17.65% traders, middlemen at 2.94%, and the owner SPB by 5.88%.The results also show that there are three main problems by the farmers in the district of Muara Muntai, (1) Prices are unstable; (2) Input production difficult to obtain; and (3) The role of farmer groups is not optimal.Keyword : Marketing Channels, Marketing Agencies, Palm Oil Farmers.